Metode Dakwah Ustadz Syafi’i dalam Meningkatkan Pemahaman Agama Pada Perwiridan Ibu-Ibu Nurul Hasanah di Tasak Lama Desa Lalang Kecamatan Medang Deras Kabupaten Batu Bara - Natasha, Putri Aulia; Azhar, (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
The da'wah method is one of the elements of da'wah which has an important and strategic role for success. The da'wah method can also be interpreted as the path or way a da'i conveys his da'wah to mad'u. The use of a correct da'wah method is a very important element in the success of a da'wah activity. Basically, in the Al-Quran surah an-Nahl verse 125, the principles of da'wah methods are stated, including the bil-hikmah da'wah method, mau'idzah hasanah da'wah. So, with this da'wah method, it is hoped that a da'wah activity can run well and be conveyed to mad'u. A religious figure must know the condition of his mad'u so that the delivery of the da'wah message remains on target. There is still a lack of religious understanding in Tasak Lama Lalang Village, this can be seen from the religious activities of Nurul Hasanah women if they are not led by an ustadz. This research aims to determine the da'wah method used by Ustadz Syafi'i in increasing understanding of religion in the preaching of Nurul Hasanah women, namely with the bil-hikmah da'wah method and the mau'idzah Hasanah da'wah method, both of which are also very closely related because they use the method This da'wah can make it easier to carry out more optimal da'wah. This research is qualitative research (field research) which is descriptive qualitative in nature. Data collection techniques use observation, interviews and documentation. So the results of the research regarding the da'wah method of religious figures/preachers are using the bil-hikmah da'wah method, the mau'idzah hasanah da'wah method. In the success of a da'wah activity, the method used in da'wah is by giving good advice, good words, not by forcing someone, let alone using harsh methods towards the object of the da'wah, and by giving a concrete example or action so that it can bring about change. which is better for the environment and can practice it in everyday life and always be on the path that is approved by Allah.
Keywords: Method Of Da'wah Bil Hikmah; Method of Da'wah Mau’idzah Hasanah; Ustadz Syafi’i, Wirid